2023
DOI: 10.1111/puar.13600
|View full text |Cite
|
Sign up to set email alerts
|

Justice in Black and Brown: The impact of political control and representative bureaucracy on street level outcomes

Abstract: This study tests the explanatory power of two prominent public administration theories-political control and representative bureaucracy-in understanding disparities in public service provision. While prior research focused on street-level bureaucracy, we study here how political and group identities of top elected law enforcement officials affect the distribution of youth arrests, alternatives, and prosecutions among minority groups. Data from Florida's 67 counties between 2015 and 2020 demonstrate that sherif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…The dataset of the study is therefore offered to the public administration scholarly community for further analysis and to further investigate the boundary conditions of symbolic representation. It is suggested that future research involve qualitative studies to understand the public's perception of the police and investigate whether the passive representation of sociodemographic identities, attitudes (e.g., liberal vis‐à‐vis conservative), or political values (see Jackson et al, 2022) would have any effects on the extent to which job applicants would find the police organizationally attractive, and to further understand boundary conditions of symbolic representation.…”
Section: Discussionmentioning
confidence: 99%
“…The dataset of the study is therefore offered to the public administration scholarly community for further analysis and to further investigate the boundary conditions of symbolic representation. It is suggested that future research involve qualitative studies to understand the public's perception of the police and investigate whether the passive representation of sociodemographic identities, attitudes (e.g., liberal vis‐à‐vis conservative), or political values (see Jackson et al, 2022) would have any effects on the extent to which job applicants would find the police organizationally attractive, and to further understand boundary conditions of symbolic representation.…”
Section: Discussionmentioning
confidence: 99%
“…Jackson, Neshkova, and Meier (2023) examine disparities in public service provision from two theoretical perspectives—political control and representative bureaucracy. Their compelling study examines whether the political and group identities of top elected law enforcement officials affect the distribution of youth arrests, alternatives, and prosecutions among minority groups.…”
Section: In This Issuementioning
confidence: 99%
“…As Palus and Yackee (2016) state, “Agency leaders often enjoy disproportionate power over policy administration’ (Krause & O'Connell, 2011, p. 2)” (p 699). However, again, much literature focuses on the bureaucratic discretion held by street‐level bureaucrats and not on the upper managerial layers of an agency (Garrow & Grusky, 2013; Jackson et al, 2022; Keulemans & Groeneveld, 2020; Meier & Bohte, 2001). Higher echelons within state agencies, for example agency heads, have yet to be analyzed with the same vigor.…”
Section: Oversight Communication and Intersectionality In Bureaucracymentioning
confidence: 99%